Participação e regulação de macrófagos na malária experimental - Tomé, Fernanda Dias (2016)
Malaria is a neglected tropical disease caused by the protozoan parasite Plasmodium sp., which is capable of infecting red blood and liver cells. Profile Th1 and Th2 cells play an important role and can determine whether there is an effective response or increased sensitivity to the disease. Several factors may act on these cells and influence the immune response, such as leptin hormone, which in high concentrations stimulates Th1 cells and consequently M1 macrophages; on the other hand, leptin low levels may favor Th2 profile and M2 macrophages polarization. The macrophages role in the experimental fatal malaria is not clearly described. Thus, this work aimed evaluate the regulation of M1 and M2 macrophages during infection with P. berghei NK65 in vitro and regulatory mechanisms, leptin and cytokines in BALB / c mice. The animals were infected with iRBCs / P. berghei and euthanized at 4; 7 or 14 d.p.i. Every two days, the mice were weighed and parasitemia was estimated; it assessed the weight of the perigonadal fat, liver and spleen for index analysis thereof, as well as macroscopic of these organs. It was performed spleen and liver histological analysis and tissue extract was transferred to cytokine assay by ELISA. Serum leptin was determined by ELISA. M1 and M2 macrophages were differentiated and placed, in vitro, in the presence of infected mice erythrocytes to evaluate phagocytosis, elimination of the parasite, urea and NO production. Our data showed that the infection led to hepatosplenomegaly, fat loss and tissue damage. Initially infection by P. berghei led to increasing leptin and Th1 cytokines, followed by a immunoregulation and increasing IL-4 and IL-10 that characterize the regulation and Th2 polarization at 14 day after infection. In vitro, infected erythrocytes were able to induce a M2 macrophages regulation, causing the same to produce NO, a characteristic molecule of M1 macrophages. Despite the NO production, there was no decrease in infection rate, indicating escapement mechanism. These data together with previous data from our group show that the experimental malaria is able to induce immunomodulation and change macrophages profiles, and that this is due to polarization of cytokine response that is directly influenced by the leptin hormone; causing tissue damage and leading to high levels of parasitaemia, perpetuating the infection and subsequent death.